Manipulate the Electronic and Magnetic States in NiCo2O4 Films through Electric‐Field‐Induced Protonation at Elevated Temperature. Issue 16 (27th February 2019) - Wang, Meng; Sui, Xuelei; Wang, Yujia; Juan, Yung‐Hsiang; Lyu, Yingjie; Peng, Huining; Huang, Tongtong; Shen, Shengchun; Guo, Chenguang; Zhang, Jianbing; Li, Zhuolu; Li, Hao‐Bo; et al.
Abstract: Ionic‐liquid‐gating‐ (ILG‐) induced proton evolution has emerged as a novel strategy to realize electron doping and manipulate the electronic and magnetic ground states in complex oxides. While the study of a wide range of systems (e.g., SrCoO2.5, VO2, WO3, etc.) has demonstrated important opportunities to incorporate protons through ILG, protonation remains a big challenge for many others. Furthermore, the mechanism of proton intercalation from the ionic liquid/solid interface to whole film has not yet been revealed. Here, with a model system of inverse spinel NiCo2 O4, an increase in system temperature during ILG forms a single but effective method to efficiently achieve protonation. Moreover, the ILG induces a novel phase transformation in NiCo2 O4 from ferrimagnetic metallic into antiferromagnetic insulating with protonation at elevated temperatures. This study shows that environmental temperature is an efficient tuning knob to manipulate ILG‐induced ionic evolution. Abstract : Ionic‐liquid‐gating‐induced protonation is realized in the inverse spinel NiCo2 O4 with an elevated environmental temperature, and has a major impact on the electronic and magnetic states. This study takes the understanding of the ionic‐liquid‐gating‐induced protonation process a step further and provides a generic strategy to boost this effect in extended material systems.